Unglazed and glazed ceramic tiles : a survey of selected suppliers and major markets - International Trade Centre UNCTAD/GATT. (Geneva : International Trade Centre, 1982)
Tiles have been used as surfacing for walls and floors for thousand of years because of their beauty and durability. This study examines tiles that are produced commercially as they form the bulk of international trade in this item.
Includes bibliographical references.
II 15/01/2019
Loans
Keywords: Tile industry; Market surveys